Young People’s Perception of Internet Pornography: Case of Junior High School Students’ in West Java Indonesia - Bona Pratamawaty, Benazir; Limilia, Putri; Prihandini, Puji (International Journal of Psychosocial Rehabilitation, 2020)
Pornography contents on the internet exists in a various kind possible that resulting in high rates of accidentally/involuntarily exposure towards internet users, e.g. pop-up ads and web banner. This is mainly how children and young people encounter pornography contents. Internet pornography exposure on children and young people has affected their perception on pornography realism beside other impacts it may occur on children and young people. This study aims to investigate young people’s perception on pornography contents and evaluate the difference between young male and young female perception towards pornography, mainly internet pornography contents. Methods used was quantitative by delivering questionnaires to 120 respondents of junior high school students in Bandung and Depok of West Java. Multistage sampling technique was employed to determine the sample. Quantitative descriptive analysis was applied to analyze primary data. Results indicate that young people found it confusing to define pornography but two predominate categories are sexual and 18+. Mostly young male define pornography as sexual while mostly young female defines it as 18+ which comprises of large scope of content types. Mostly both young male and young female view pornography negatively but small numbers of young male view it positively indicates permissive attitude towards pornography contents.